One woman in the war : Hungary, 1944-1945 - Polcz, Alaine; Tezla, Albert (Budapest ; New York : C E U Press, 2002)
"This autobiographic account of the experiences of a woman, then 19-20, in the closing months of the Second World War was first published in Hungarian in 1991 and has since been translated into a number of languages. Exciting, shocking and revealing, it is a journey into a piece of Central European history and a testament to the fighting spirit of a woman whose every moment was a challenge and protest against the inhumanity of war."--Jacket
The honeymoon -- A refugee's idyll -- The front -- Peace.
English.
eBooks on EBSCOhost
Keywords: Polcz, Alaine; Polcz, Alaine; World War, 1939-1945 -- Personal narratives, Hungarian; World War, 1939-1945 -- Hungary; Refugees -- Hungary; World War, 1939-1945 -- Hungary -- Personal narratives, Hungarian; Refugees; Guerre mondiale, 1939-1945 -- Hongrie; Réfugiés -- Hongrie; Réfugiés.; refugees; Refugees; Hungary; 1939-1945; autobiographies (literary works); Personal narratives; Autobiographies; Personal narratives -- Hungarian; Autobiographies; Personal narratives; Autobiographies; Récits personnels